2008
DOI: 10.1093/toxsci/kfn198
|View full text |Cite
|
Sign up to set email alerts
|

Global Liver Proteomics of Rats Exposed for 5 Days to Phenobarbital Identifies Changes Associated with Cancer and with CYP Metabolism

Abstract: A global proteomics approach was applied to model the hepatic response elicited by the toxicologically well-characterized xenobiotic phenobarbital (PB), a prototypical inducer of hepatic xenobiotic metabolizing enzymes and a well-known nongenotoxic liver carcinogen in rats. Differential detergent fractionation two-dimensional liquid chromatography electrospray ionization tandem mass spectrometry and systems biology modeling were used to identify alterations in toxicologically relevant hepatic molecular functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 83 publications
0
12
0
2
Order By: Relevance
“…In contrast to CAR that is primarily found in the cytosol [44], PXR is primarily found in the nucleus and inactive PXR may form repressor complexes with SMRT or SHP and histone deacetylases, and inhibit transcription [45, 46]. Ligand activation releases the co-repressors and initiates the recruitment of co-activators such as steroid receptor co-activator 1 (SRC-1) and histone acetylases that promote transcription [4547] (Fig.…”
Section: Activation and Promiscuity Of Pxr And Carmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to CAR that is primarily found in the cytosol [44], PXR is primarily found in the nucleus and inactive PXR may form repressor complexes with SMRT or SHP and histone deacetylases, and inhibit transcription [45, 46]. Ligand activation releases the co-repressors and initiates the recruitment of co-activators such as steroid receptor co-activator 1 (SRC-1) and histone acetylases that promote transcription [4547] (Fig.…”
Section: Activation and Promiscuity Of Pxr And Carmentioning
confidence: 99%
“…Barbituates have historically been correlated with liver tumor formation in murine experiments [173175], and an increase in CAR expression in G1 phase is associated with cell proliferation [176]. Further, a global proteomics study following PB-treatment of wild-type rats found that a possible mechanism for carcinogenesis was through increased xenobiotic metabolism enzymes, especially CYP2B and other oxidoreductases, increased cell cycle activity, and a general induction of several pro-carcinogenic proteins [44]. PB was also prescribed to patients with hepatic injury due to its ability to decrease the time for hepatic regeneration, and CAR activation by PB or TCPOBOP has been correlated with hepatomegaly of the liver in response to toxicants.…”
Section: Hepatocarcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…В ряде работ идентификация цитохромов Р450 была получена в рамках общего протеомного анализа [24][25][26]. Так, в работе [24] при протеомном анализе эндоплазматического ретикулума пораженных опухолью, индуцированной афлатоксином В1, тканей печени крыс обнаружено уменьшение экспрессии цитохромов Р450 по сравнению с контрольными образцами.…”
Section: идентификация цитохромов р450 в биологических объектахunclassified
“…Так, в работе [24] при протеомном анализе эндоплазматического ретикулума пораженных опухолью, индуцированной афлатоксином В1, тканей печени крыс обнаружено уменьшение экспрессии цитохромов Р450 по сравнению с контрольными образцами. В работах [25,26] методами 2D-LC исследован эффект увеличения экспрессии цитохромов Р450 в печени крысы после введения животным фенобарбитала. В работе [26] показано, что при общем увеличении содержания цитохромов наибольший эффект наблюдается для изоформы CYP 2В2.…”
Section: идентификация цитохромов р450 в биологических объектахunclassified